Anatomy and biomechanics of the medial patellotibial ligament: A systematic review. Issue 5 (October 2021) - Felli, Lamberto; Alessio-Mazzola, Mattia; Lovisolo, Stefano; Capello, Andrea Giorgio; Formica, Matteo; Maffulli, Nicola
Abstract: Background: The knowledge of the anatomy and biomechanics of patellar stabilizers is mandatory to achieve good clinical results with surgical reconstructive procedures. Few articles provide clear anatomical and biomechanical picture of medial patello-tibial ligament (MPTL). Methods: After a systematic review of the literature we selected in vivo or ex vivo studies providing anatomical or biomechanical measurements. We included 7 studies about MPTL anatomy for a total of 96 knees and 4 biomechanical studies. Results: The MPTL is a true ligament and important component of the medial patellar stabilizers, together with the medial patello-femoral ligament (MPFL) and medial patello-meniscal ligament. The contribution of MPTL on restriction forces of the patello-femoral joint is still unclear. Quadriceps, patellar, semitendinous and gracilis tendons are adequate grafts for surgical MPTL reconstruction. Conclusions: MPTL is a well defined anathomical structure and histologically can be considered a ligament. It plays an important role in patellar stability especially it has a main role on patellar rotation and tilt instead on shift. Highlights: The medial patellotibial ligament is an important patellar stabilizer. MPTL is a well defined anatomical structure and histologically can be considered a ligament.